Epidemiology of injuries in National Collegiate Athletic Association women's field hockey: 2014-2015 through 2018-2019 - Nedimyer, A. K.; Boltz, A. J.; Robison, H. J.; Collins, C. L.; Morris, S. N.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association has sponsored women's field hockey since 1981, and team membership as well as student-athlete participation has grown over time. Background: Routine examinations of injuries sustained by athletes are important for identifying and understanding patterns that can be used to inform sport safety practices. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program from 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 6.27 per 1000 athlete-exposures (AEs). Head/face injuries (16.0%) and thigh injuries (12.3%) were the most commonly injured body parts during the 2014-2015 through 2018-2019 academic years. Concussion (8.6%) was the most commonly reported injury, and concussion rates notably decreased between 2017-2018 and 2018-2019. Summary: Study findings were generally consistent with the existing epidemiologic evidence. Incidence rates and trajectories of commonly observed injuries warrant particular attention in the future.